Sex differences in emotional perception: Evidence from population of Tuvans (Southern Siberia) - Mezentseva, A. A.; Rostovtseva, V. V.; Ananyeva, K. I.; Demidov, A. A.; Butovskaya, M. L. (Frontiers in Psychology, 2022)
Our goal was to explore sex differences in estimations of emotional states through static facial expressions. Previously, it was reported that women outperform men in non-verbal communication, including recognition of emotions through facial expressions. Here, using a «two-culture» approach, we investigated sex differences in perception of emotional facial expressions through photographs. The study was conducted among Tuvans, people from Southern Siberia of Mongolian origin. The respondents were presented with a set of photographs of men and women of European and Tuvan origin, demonstrating four basic emotions: happiness, anger, fear, and disgust. All subjects were asked to answer the question: «What does the person in the photo feel? ». We have found that the Tuvans easily identified happiness and anger, however, the accuracy of fear and disgust recognition was low. No sex differences in the recognition of happiness, disgust and fear have been revealed. However, anger recognition was significantly moderated by the sex and origin of the models as well as the perceiver’s sex. Tuvan women were significantly less accurate identifying anger in male Tuvans, compared to Tuvan men. Besides, the recognition of fear was significantly affected by the perceiver’s age and the models’ origin. The older were the Tuvan perceivers, the less accurate they were in recognition of fear in both male and female Tuvans. This study revealed the inverse variant of sexual differences in the recognition of non-verbal signals of anger, thus, raising the question of the role of cultural factors in the perception of «basic» emotional facial expressions.